Evaluation of the efficacy of injectable chondroitin sulfate for knee osteoarthritis in real clinical practice - E. Yu. Pogozheva; A. E. Karateev (Современная ревматология, 2019)
Objective: to carry out a statistical analysis of clinical material obtained in an open-label observational study of the efficacy and safety of injectable chondroitin sulfate (ICS) in real clinical practice.Patients and methods. A total of 170patients with knee osteoarthritis (OA) (78.8% females; mean age, 60.5+8.3 years) who experienced severe pain and needed to regularly take non-steroidal antiinflammatory drugs (NSAIDs) were examined. All the patients received a cycle of therapy with ICS (25 intramuscular injections every other day). The treatment results were assessed by the changes of pain intensity at rest and during movement and general health status (a 100 mm visual analogue scale) at 2 months after therapy initiation. The dynamics of NSAID use, therapy tolerance, and patient assessment of treatment outcomes were also taken into account.Results and discussion. There were decreases in the median severity of pain at rest from 40.0 [20.0; 70.0] to 10.0 [0.0; 20.0] mm, in pain during movement from 65.0 [58.0; 80.0] to 20.0 [10.0; 30.0] mm, and in overall health status assessment from 60.0 [50.0; 70.0] to 20.0 [10.0; 40.0] mm (p < 0.001). It might be possible to discontinue NSAIDs or to reduce their dose/frequency in 87.9% of patients. 83.3% of patients rated their treatment results as good and excellent. No serious adverse reactions were observed.Such a beneficial effect of therapy should be taken with some caution, since it has been obtained during an open-label uncontrolled observational study. Although the injection of this type of pharmacological agents is practically not used in Western countries; Russia has meaningful and generally positive experience with injectable slow-acting symptom-modifying drugs (SMDs), including CS. The advantages of this procedure are an enhanced bioavailability of SMDs, an accelerated onset of an analgesic effect, and higher patient adherence to therapy. Conclusion. The findings showed the good efficacy and tolerance of ICS in patients with knee OA in real clinical practice.